TEMPORAL ASSOCIATIONS OF LATEROPULSION RESOLUTION AND BALANCE RECOVERY AFTER HEMISPHERIC STROKES - Delva, I.I.; Oksak, O.M.; Delva, M.Yu. (World of Medicine and Biology, 2024)
Disorder of body orientation with respect to gravity is one of the key elements that impairs balance control in post-stroke patients. We investigated the temporal associations between the normalization of body orientation in the frontal plane and balance recovery after hemispheric strokes. We included in the study patients with hemispheric strokes occurring within the last month. 53 patients had lateropulsion and 7 patients had pusher syndrome, according to the Scale for Contraversive Pushing. Patients were subsequently invited for a weekly examination until the body's verticality was normalized. At each visit, the balance status was assessed. Recovery of balance control depended on the normalization of body orientation in the frontal plane. Recovery of the sitting and standing balance was maximal during the weeks of transition of pusher syndrome into lateropulsion and during the weeks of resolution of lateropulsion into uprightness.
Keywords: hemispheric stroke; lateropulsion; pusher syndrome; balance; recovery